Woman no. 17 [compact disc, unabridged] : a novel - Lepucki, Edan (Books on Tape ; Random House Audio, 2017)
Hiring a live-in nanny to attend her family's needs while she attempts to finish writing her book, Lady Daniels begins questioning the young woman's agenda when the latter instantly connects with the family and begins acting in suspicious ways.